Line-based calibration of a micro-vision motion measurement system. (June 2017) - Li, Hai; Zhang, Xianmin; Wu, Heng; Gan, Jinqiang
Abstract: We propose a flexible and practical line-based method for calibrating a micro-vision motion measurement system by using a resolution target, considering the lens distortion. First, centerlines of the stripes in the image of resolution target are extracted with an improved center gravity approach. Then distortion coefficients are obtained through the nonlinear optimization, utilizing straightness of the lines. Finally, these lines are corrected and used for estimating parameters of the system. Two experiments are conducted to validate the effectiveness of the proposed method. The results demonstrate that our method is effective and practical for calibrating the micro-vision measurement system. Highlights: A flexible method for calibration of the micro-vision motion measurement system is proposed. Line feature is used in this method to improve the operability and flexibility. Both the intrinsic and extrinsic parameters can be obtained after implementing this approach. The absolute accuracy has apparently improved after the calibration. This method has the capability to calibrate multi-cameras vision system.